Coloration in Supraparticles Assembled from Polyhedral Metal‐Organic Framework Particles. (23rd February 2022) - Wang, Junwei; Liu, Yang; Bleyer, Gudrun; Goerlitzer, Eric S. A.; Englisch, Silvan; Przybilla, Thomas; Mbah, Chrameh Fru; Engel, Michael; Spiecker, Erdmann; Imaz, Inhar; Maspoch, Daniel; Vogel, Nicolas
Abstract: Supraparticles are spherical colloidal crystals prepared by confined self‐assembly processes. A particularly appealing property of these microscale structures is the structural color arising from interference of light with their building blocks. Here, we assemble supraparticles with high structural order that exhibit coloration from uniform, polyhedral metal–organic framework (MOF) particles. We analyse the structural coloration as a function of the size of these anisotropic building blocks and their internal structure. We attribute the angle‐dependent coloration of the MOF supraparticles to the presence of ordered, onion‐like layers at the outermost regions. Surprisingly, even though different shapes of the MOF particles have different propensities to form these onion layers, all supraparticle dispersions show well‐visible macroscopic coloration, indicating that local ordering is sufficient to generate interference effects. Abstract : Supraparticles exhibiting coloration and high structural order are assembled from four different uniform, polyhedral metal–organic framework (MOF) particles. In these supraparticles, the macroscopic color originates from constructive interference of light reflected at ordered surface layers of the polyhedral particles.